Florida Crop/Pest Management Profile: Avocado - Mark A. Mossler; Jonathan H. Crane (EDIS, 2008)
Revised! Circular 1271, a 10-page fact sheet by Mark A. Mossler and Jonathan H. Crane, profiles the avocado industry in Florida - production facts, regions and practices, and pest management strategies. Includes references and key contacts. Published by the UF Pesticide Information Office, Horticultural Sciences Department, September 2008.